Guerras e conflitos vinculados ao uso das águas: Grotius e os desdobramentos modernos e contemporâneos da questão - Almeida, Sizinio Lucas Ferreira de (2017)
The present work aims at examining the issue of conflicts over natural resources, especially water, in modern philosophical reflection, and some of its contemporary developments. To do so, we will start from the reflections of the Dutch jurist and philosopher Hugo Grotius on the attempts to privatize the seas in the seventeenth century, exposed both in Mare Liberum (1609) and in the law of war and peace (1625), and conflicts and wars Generated as a result. In a second moment we will examine the reception of this debate by the Geneva philosopher Jean Jacques Rousseau in the eighteenth century, and the developments through the theories of contemporary authors such as Maude Barlow in the works Water: blue pact (2009) and Water: future blue (2015) and Michel Serres, in the works Natural contract (1991) and the War against the world (2011). These examine the current conflicts and wars motivated by the misuse of natural resources and attempts to privatize water, contrary to what the authors propose to be considered as a human right to water and which is based on the modern debate about natural law.